Strategi Lembaga Adat Desa (LAD) dalam Revitalisasi Cagar Budaya Batak Toba di Desa Lumban Gaol, Kecamatan Balige, Kabupaten Toba - Dina Serema Samosir; Martua Sihaloho; Roida Lumbantobing; Masniar Hernawati Sitorus; Wensdy Sitindaon (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This research aims to determine how the Village Customary Institution (LAD) strategies for revitalizing cultural heritage in Lumban Gaol Village. Whether the existence of the Village Customary Institution can revive cultural heritage and its impact on the surrounding community. This research was conducted in Lumban Gaol Village using qualitative research methods and informants who became informants, namely the chairman of the Village Customary Institution (LAD), village head, and community. Data collection techniques were carried out through observation, interviews, documentation, and drawing conclusions. The research results show that the strategies carried out by the Village Customary Institution (LAD) in revitalizing cultural heritage in Lumban Gaol Village include socialization strategies, namely LAD conducting socialization regarding the importance of preserving customs and culture. Culture experience, namely LAD inviting young people to clean cultural heritage and inviting children and the elderly to participate in the Cultural and Tourism Awareness Community in Lumban Gaol Village. Economic strategy, namely LAD together with the community building the village by managing cultural heritage to become a source of income for the community. Conservation strategy, namely LAD together with the community improving road access and repairing buildings by painting, renovating damaged ones, and beautifying the buildings so that the community or visitors feel safe and comfortable.